THE RELATIONSHIP BETWEEN ANEMIA INCIDENCE IN PREGNANT MOTHERS AND LOW BIRTH WEIGHT BABY DELIVERY - Altin Sutni; Jasmawati Jasmawati; Lukman Nulhakim (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Anemia is a condition in which the number of red blood cells (erythrocytes) is less than it should be even though red blood cells contain hemoglobin which is responsible for distributing nutrients and oxygen throughout the body Anemia in pregnancy can cause miscarriage, premature birth, low birth weight, bleeding before and after childbirth can even cause death of mother and child. The purpose of this study was to determine the relationship between the incidence of anemia in pregnant women and LBW births at UPT Puskesmas Kaliorang in 2023. This research is a type of analytic observational research with a retrospective approach. The population in this study were pregnant women at UPT Puskesmas Kaliorang. The number in this study was 15 people, the sampling technique used was total sampling. The instruments in this study were observation sheets, medical records, laboratory results sheets. Data analysis using chi-square. The results of statistical tests using the Chi-square test on the variable anemia with LBW incidence showed that the p-value = 0.001 and the Odds Ratio value (OR = 27.500). There is a relationship between the incidence of anemia in pregnant women and LBW births with a risk level of 27 times greater. Anemia can be prevented by consuming a balanced nutritious diet with sufficient intake of iron to meet the body's needs. Iron can be obtained by consuming meat (especially red meat) such as beef.